2022
DOI: 10.3390/microorganisms10030606
|View full text |Cite
|
Sign up to set email alerts
|

Novel Salmonella Phage, vB_Sen_STGO-35-1, Characterization and Evaluation in Chicken Meat

Abstract: Salmonellosis is one of the most frequently reported zoonotic foodborne diseases worldwide, and poultry is the most important reservoir of Salmonella enterica serovar Enteritidis. The use of lytic bacteriophages (phages) to reduce foodborne pathogens has emerged as a promising biocontrol intervention for Salmonella spp. Here, we describe and evaluate the newly isolated Salmonella phage STGO-35-1, including: (i) genomic and phenotypic characterization, (ii) an analysis of the reduction of Salmonella in chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…To determine SNPs in the lytic phage STGO-35-1, we sequenced phage isolated from day 1 and 21. A comprehensive report of genomic characteristics of this phage was recently reported ( Rivera et al., 2022 ) and a short time exposure showed SNPs in receptor binding proteins. Further, in this study, we also identified two SNPs in sequenced phage from day 21, and these two SNPs were found in genes annotated as tails spike proteins, which are involved in recognizing the membrane receptors in the bacteria.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…To determine SNPs in the lytic phage STGO-35-1, we sequenced phage isolated from day 1 and 21. A comprehensive report of genomic characteristics of this phage was recently reported ( Rivera et al., 2022 ) and a short time exposure showed SNPs in receptor binding proteins. Further, in this study, we also identified two SNPs in sequenced phage from day 21, and these two SNPs were found in genes annotated as tails spike proteins, which are involved in recognizing the membrane receptors in the bacteria.…”
Section: Resultsmentioning
confidence: 94%
“…(2018 ). A complete description of the used phage, annotation, and growth conditions is in Rivera et al. (2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, Salmonella spp. is thought to be responsible for 155,000 fatalities and 93.8 million instances of acute gastroenteritis [82,83]. According to the Centers for Disease Control and Prevention (CDC), Salmonella spp.…”
Section: Salmonellosismentioning
confidence: 99%